Optic Nerve Decompression for Orbitofrontal Fibrous Dysplasia - Abe, Takumi (2002)
Orbitofrontal fibrous dysplasia often involves the bony orbit and the optic canal. Although fibrous dysplasia reportedly produces compression of the optic nerve leading to visual distrubances, optic nerve decompression in patients without clinical signs of optic neuropathy is still controversial. We describe two patients with orbitofrontal fibrous dysplasia without signs of visual disturbance and one patient with McCune-Albright syndrome and progressive visual impairment. Optic nerve decompression was performed prophylactically for two patients and therapeutically for one patient through the transcranial extradural route. Dystopias and craniofacial deformities induced by fibrous dysplasia also were corrected. The micropressure suction-irrigation system was especially effective for decreasing heat transfer and thereby preventing thermal injury of the optic nerve. The orbitofrontal area was reconstructed from cranial bone, iliac bone, and ribs. Postoperative follow-up revealed no disturbances in visual function and no evidence of cerebrospinal fluid leakage. These findings suggest that optic nerve decompression may be effective in preventing visual disturbances with minimal risk of other neurological sequelae. Subsequent orbital reconstruction yielded satisfactory cosmetic results.